(untitled) (Journal of the College of Basic Education, 2023)
In the 21st century, the advancement of technology plays essential role in the field of education and schooling. The term e-learning refers to electronic learning which an alternative of the traditional education system is. Subjects and methods:In this study, eighty four second stage EFL students at College of Arts, AL Mustansiriyha University randomly allocated into two groups. The first group (n=43) received New words of the English textbook without using E-Learning. The second group (n=41) involved the use of E- Learning to enhance vocabulary and grammar skills for the same period and served as the interventional group. This study adopted (pretest- posttest).. After the end of the tests,; the results have been analyzed. Results The researcher compared the mean score of the EG (45.302) and that of the CG (41.024). By utilizing the t-test formula for two independent samples, it has found that the computed t-value is 3.376, which is higher than the tabulated t-value (1.99), at the 0.05 level of significance and 82 degrees of freedom. That indicates there is a statistically significant difference between the two groups in favor of the EG. Conclusion The use of E- Learning could enhance vocabulary and Grammar skills in Iraqi universities English students.